Battery pack cover, battery pack unit and electric mobility
The battery pack cover, incorporating an inorganic fiber molded body with high tensile strength and a metal substrate, addresses the challenge of thermal runaways in electric vehicles by providing excellent flame-blocking properties without compromising loading performance.
Patent Information
- Application Number
- JP2022569888
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-14
- Filing Date
- 2021-12-07
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-12-07
AI Technical Summary
The increasing energy density of battery modules in electric vehicles leads to higher heat generation and a greater risk of thermal runaways, necessitating a battery pack cover with enhanced flame shielding properties without compromising loading performance.
A battery pack cover featuring an inorganic fiber molded body with a tensile strength of 20N or more, combined with a metal substrate, providing excellent flame-blocking properties and resistance to thermal blasts.
The battery pack cover effectively prevents flames from penetrating, offering superior flame-blocking properties while maintaining loading performance, thus enhancing safety in electric mobility applications.
Smart Images

Figure 0007657832000002 
Figure 0007657832000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a battery pack cover, a battery pack unit, and an electric mobility device. [Background technology]
[0002] A battery pack unit used in electric mobility such as an electric vehicle has a housing with a part of the housing being an open part, a battery pack arranged in the housing, and a battery pack cover that closes the open part (Patent Document 1: WO2012 / 167921). Paragraph 0081 of Patent Document 1 lists aluminum, aluminum alloy, magnesium, magnesium alloy, AlSiC, titanium, titanium alloy, steel, stainless steel, and special steel as examples of materials that may be used for the battery pack cover.
[0003] 2. Description of the Related Art In battery modules used in mobility such as electric vehicles, a heat insulating material or a heat absorbing material may be provided between battery cells as a measure against thermal runaway of the battery.
[0004] Patent Document 2 (EP2506336A1) discloses a battery pack thermal management system for minimizing the effects of thermal runaway, which includes a plurality of batteries and an airtight battery pack packaging, the battery pack packaging having a cavity and a gas exhaust port on its outer wall, and which is configured so that when at least one battery experiences thermal runaway, the gas exhaust port allows gas to pass to the outside of the battery pack packaging.
[0005] Also, a battery unit is known in which a mica sheet or the like is attached to the side surface of a battery pack cover that covers a battery module in order to improve fire resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2012 / 167921 [Patent Document 2] European Patent Application Publication No. 2506336 Summary of the Invention [Problem to be solved by the invention]
[0007] In order to extend the driving distance, the energy density of the battery module mounted on the electric vehicle tends to increase, and the demand for heat generation and thermal runaway risk of the battery is increasing. In the event of a fire that cannot be suppressed by the heat insulating material provided between the battery cells, the object of the present invention is to provide a battery pack cover with excellent flame-blocking properties to delay the spread of the fire to the interior members. Furthermore, the object of the present invention is to provide a battery pack unit using this battery pack cover and an electric mobility using this battery pack unit. [Means for solving the problem]
[0008] Mica sheets are a hard and fragile mineral, and are therefore easily damaged by vibrations caused by driving. In addition, the weight of the vehicle increases as functions such as flame resistance are satisfied. On the other hand, a lightweight flame-resistant structure is easily blown away by an explosion, and does not have sufficient flame resistance to stop flames erupting from the battery pack. The inventors of the present invention have found that an inorganic fiber molded body having a tensile strength within a specific range can withstand an explosion erupting during thermal runaway of the battery and prevent flames from penetrating, and have found that it is possible to improve the flame resistance of a battery pack cover without impairing loading capacity. The present invention has the following gist.
[0009] [1] A battery pack cover for use with a battery pack, comprising: A battery pack cover comprising a cover substrate and an inorganic fiber molded body having a tensile strength of 20 N or more in the following tensile test. <Tensile Test> A test piece 25 mm wide x 160 mm long is cut out from the inorganic fiber molded product, and pulled in the longitudinal direction at a speed of 25 mm / min using a tensile tester. The maximum load measured is taken as the tensile strength.
[0010] [2] The battery pack cover described in [1], wherein the cover substrate is a metal substrate.
[0011] [3] The battery pack cover according to [1] or [2], which is a laminate formed by stacking the cover base material and the inorganic fiber molded body.
[0012] [4] A battery pack cover according to any of [1] to [3] that is not penetrated by a flame test at a flame temperature of 1000°C for 5 minutes.
[0013] [5] The battery pack cover according to any one of [1] to [4], wherein the inorganic fiber molding is composed of inorganic fibers with an average fiber length of 3 mm or more.
[0014] [6] The battery pack cover according to any one of [1] to [5], wherein the inorganic fiber molding is a woven fabric or a nonwoven fabric.
[0015] [7] The battery pack cover according to any one of [1] to [6], wherein the inorganic fiber molding is a needle blanket.
[0016] [8] A battery pack unit having a battery pack cover and a battery pack according to any one of [1] to [7].
[0017] [9] The battery pack unit according to [8], A battery pack unit in which the inorganic fiber molding of the battery pack cover is disposed on the battery pack side.
[0018]
[10] An electric mobility vehicle equipped with a battery pack unit according to [8] or [9]. Effect of the Invention
[0019] The inorganic fiber molded body used in the present invention has a tensile strength of 20N or more and is capable of preventing thermal runaway of a battery. Therefore, the inorganic fiber molded body has excellent properties of preventing flames from penetrating the Battery pack The cover has excellent flame retardant properties. [Brief description of the drawings]
[0020] [Figure 1] FIG. 2 is a schematic cross-sectional view of a battery pack unit. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The battery pack cover of the present invention is used for a battery pack unit. The battery pack unit includes a battery pack and a battery cover.
[0022] 1 is a schematic cross-sectional view showing an example of a battery pack unit. The battery pack unit 1 further includes a housing 2 having an open portion 2a, a battery pack cover 3 that closes the open portion 2a, and a battery pack 10 disposed within the housing 2. However, the housing is not necessarily required.
[0023] The battery pack cover 3 has an inorganic fiber molded body 4 and a cover base material 5. The inorganic fiber molded body 4 and the cover base material 5 are both plate-shaped and overlapped. However, they may be bonded together with an adhesive. The inorganic fiber molded body 4 is disposed on the inside of the battery pack unit 1 with respect to the cover base material 5.
[0024] The battery pack 10 disposed in the housing 2 includes a plurality of battery modules 11.
[0025] This battery pack unit 1 can improve the flame-proofing of the battery pack cover without impairing the loading capacity, and is therefore suitable for use in batteries for electric mobility such as electric cars, electric motorcycles, and ships. The battery is not particularly limited, and examples thereof include secondary batteries such as lithium ion batteries, nickel-hydrogen batteries, lithium-sulfur batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, sodium-sulfur batteries, lead-acid batteries, and air batteries. Of these, lithium ion batteries are preferred, and the battery pack unit 1 is particularly suitable for use in suppressing thermal runaway of lithium ion batteries.
[0026] [Cover material] The cover substrate 5 of the battery pack cover 3 is not particularly limited, and may be a housing material such as a metal substrate or a reinforced resin substrate. From the viewpoint of flame resistance, a metal substrate is preferred, and aluminum, aluminum alloy, magnesium, magnesium alloy, titanium, titanium alloy, iron, stainless steel, etc. are suitable. The thickness of the metal substrate 5 is preferably about 0.1 to 10 mm, particularly about 0.3 to 7 mm, but is not limited thereto.
[0027] [Inorganic fiber molded body] The inorganic fiber molded product used in the present invention has a tensile strength of 20 N or more, preferably 25 N or more, and particularly preferably 30 N or more. The higher the tensile strength of the inorganic fiber molded product, the better, and there is no upper limit, but it is preferably 100 kN or less, and particularly preferably 50 kN or less. The tensile strength is a value measured by the method described in the Examples below.
[0028] The inorganic fibers constituting the inorganic fiber molded body are not particularly limited, and examples thereof include single or composite fibers of silica, alumina / silica, and zirconia, spinel, titania, etc., containing these. The inorganic fibers are preferably alumina / silica-based fibers, and particularly preferably crystalline alumina / silica-based fibers. The alumina / silica composition ratio (weight ratio) of the alumina / silica-based fibers is preferably in the range of 60-95 / 40-5, more preferably in the range of 70-84 / 30-16, and particularly preferably in the range of 70-76 / 30-24.
[0029] The inorganic fibers preferably have an average fiber length of 1 mm or more, more preferably 2 mm or more, and even more preferably 3 mm or more. 3 mm or less, preferably 1.0×10 3 The inorganic fibers have an average fiber diameter of 3 to 10 μm, and preferably 5 to 8 μm. If the average fiber length and average fiber diameter of the inorganic fibers are within this range, the inorganic fiber molded product will have high tensile strength, which is preferable. If the average fiber length and average fiber diameter of the inorganic fibers are within this range, the amount of dust suspended in the air can be reduced, which is preferable. The average fiber length of the inorganic fibers is the average value of 300 fibers measured by observation under a microscope. The average fiber diameter is the average value of 100 fibers measured by observation under a microscope.
[0030] The inorganic fiber molded body used in the present invention is not limited in its manufacturing method or shape as long as it has the desired tensile strength, but is preferably, for example, made of inorganic fibers and is a woven fabric or nonwoven fabric. When the inorganic fiber molded body is a woven fabric made of inorganic fibers, its manufacturing method is not limited, and a known method of weaving into a woven fabric can be applied. Even when the inorganic fiber molded body is a nonwoven fabric made of inorganic fibers, its manufacturing method is not limited, but it is preferably a needle blanket that has been subjected to a needling treatment. By performing the needling treatment, needle marks are formed on the inorganic fiber molded body. The inorganic fiber molded body is in a mat shape having a predetermined thickness. Hereinafter, the surface perpendicular to the thickness direction of the inorganic fiber molded body may be referred to as the mat surface. In addition, the side surface (surface in the thickness direction) perpendicular to the mat surface of the inorganic fiber molded body may be referred to as the end surface.
[0031] In one embodiment of the present invention, the inorganic fiber molded body has needle marks. The density of needle marks is determined by the unit area (1 cm 2 ) means the number of needle marks per
[0032] When visible light is applied to the matte surface of the inorganic fiber molding, the amount of light transmitted through the needle marks is greater than the amount of light transmitted through areas other than the needle marks, so the transmitted light is observed as light spots on the peeled surface. The number of light spots due to transmission through the peeled surface is counted to determine the number of needle marks.
[0033] In the present invention, the unit area (1 cm ) of the matte surface of the inorganic fiber molded product 2 The number of needle marks per square centimeter (needle mark density) is preferably 1 per square centimeter on the average of the entire mat surface. 2 More preferably, 3 / cm 2 More than 100 particles / cm 2 Less than or equal to 50 / cm 2 The following is the result.
[0034] The basis weight (mass per unit area) of the inorganic fiber molded body is 50g / m 2 More than 80g / m 2 More preferably, 100 g / m 2 More preferably, 200 g / m 2 More preferably, 400 g / m 2 The basis weight of the inorganic fiber molded body is preferably 3000 g / m 2 More preferably, 2500 g / m or less 2 Less than 2000 g / m 2 The following is the result.
[0035] The thickness of the inorganic fiber molded body is preferably 0.1 mm or more, more preferably 0.3 mm or more, and particularly preferably 0.5 mm or more. The thickness of the inorganic fiber molded body is preferably 25 mm or less, more preferably 20 mm or less, and particularly preferably 15 mm or less. When the basis weight and thickness of the inorganic fiber molded body are within these ranges, the tensile strength of the inorganic fiber molded body is in an appropriate range, which is preferable. Also, this is preferable from the viewpoint of loading capacity and space efficiency in mobility.
[0036] The basis weight and thickness of the inorganic fiber molded product can be set within the above range by adjusting the amount of fiber per unit area when the inorganic fiber aggregates constituting the inorganic fiber molded product are stacked by a folding device.
[0037] [Method of manufacturing inorganic fiber molded body] The inorganic fiber molded body can be produced by a method including a step of obtaining a mat-like aggregate of inorganic fiber precursors by a sol-gel method, a step of subjecting the obtained mat-like aggregate of inorganic fiber precursors to a needling treatment, and a firing step of firing the needling-treated mat-like aggregate of inorganic fiber precursors to obtain an inorganic fiber molded body. However, the inorganic fiber molded body may be produced by a method other than the above.
[0038] An example of a method for producing this inorganic fiber molded body will be explained below by taking as an example a method for producing an alumina / silica-based fiber molded body. However, the inorganic fiber molded body of the present invention is not limited to an alumina / silica-based fiber molded body and may be a molded body made of silica, zirconia, spinel, titania or composite fibers thereof, as described above.
[0039] <Spinning process> To produce a mat-like aggregate of alumina / silica-based fibers by the sol-gel method, a spinning solution containing basic aluminum chloride, a silicon compound, an organic polymer as a thickener, and water is first spun by a blowing method to obtain an aggregate of alumina / silica fiber precursors.
[0040] <Preparation of spinning solution> Basic aluminum chloride; Al(OH) 3-x Cl xcan be prepared, for example, by dissolving metallic aluminum in an aqueous solution of hydrochloric acid or aluminum chloride. The value of x in the above chemical formula is usually 0.45 to 0.54, preferably 0.5 to 0.53. As the silicon compound, silica sol is preferably used, but other water-soluble silicon compounds such as tetraethyl silicate and water-soluble siloxane derivatives can also be used. As the organic polymer, for example, water-soluble polymer compounds such as polyvinyl alcohol, polyethylene glycol, and polyacrylamide are preferably used. The degree of polymerization of these is usually 1000 to 3000.
[0041] The spinning solution preferably has a ratio of aluminum derived from the basic aluminum chloride to silicon derived from the silicon compound, calculated as a weight ratio of Al2O3 to SiO2, of usually 99:1 to 65:35, and preferably 99:1 to 70:30, an aluminum concentration of 170 to 210 g / L, and an organic polymer concentration of 20 to 50 g / L.
[0042] If the amount of silicon compounds in the spinning solution is less than the above range, the alumina that constitutes the short fibers tends to turn into α-alumina, and the short fibers tend to become embrittled due to the coarsening of the alumina particles. On the other hand, if the amount of silicon compounds in the spinning solution is more than the above range, the amount of silica (SiO2) produced together with mullite (3Al2O3·2SiO2) increases, and heat resistance tends to decrease.
[0043] When the aluminum concentration in the spinning solution is less than 170 g / L or the organic polymer concentration is less than 20 g / L, the spinning solution does not have a suitable viscosity, and the fiber diameter of the resulting alumina / silica-based fiber is small. That is, as a result of too much free water in the spinning solution, the drying speed during spinning by the blowing method is slow, the stretching proceeds excessively, the fiber diameter of the spun precursor fiber changes, and short fibers with a predetermined average fiber diameter and a sharp fiber diameter distribution cannot be obtained. Moreover, when the aluminum concentration is less than 170 g / L, the productivity decreases. On the other hand, when the aluminum concentration exceeds 210 g / L or the organic polymer concentration exceeds 50 g / L, the viscosity is too high to form a spinning solution. The preferred aluminum concentration in the spinning solution is 180 to 200 g / L, and the preferred organic polymer concentration is 30 to 40 g / L.
[0044] The spinning solution is prepared by adding a silicon compound and an organic polymer to an aqueous solution of basic aluminum chloride in amounts that will give the above-mentioned Al2O3:SiO2 ratio, and concentrating the solution so that the concentrations of aluminum and the organic polymer are within the above-mentioned ranges.
[0045] Blowing Spinning (fibrillation of the spinning solution) is usually carried out by a blowing method in which the spinning solution is supplied into a high-speed spinning air stream, thereby obtaining an alumina short fiber precursor. The structure of the spinning nozzle used in the above spinning is not particularly limited, but it is preferable to use a structure in which the air stream blown out of the air nozzle and the spinning solution stream pushed out of the spinning solution supply nozzle are parallel flows, and the parallel air flows are sufficiently rectified to come into contact with the spinning solution, as described in Japanese Patent No. 2602460.
[0046] In spinning, it is preferable that a fiber is first formed by sufficiently drawing the spinning solution under conditions in which evaporation of water and decomposition of the spinning solution are suppressed, and then the fiber is promptly dried. For this purpose, it is preferable to change the atmosphere from a state that suppresses evaporation of water to a state that promotes evaporation of water during the process in which the fiber is formed from the spinning solution and reaches the fiber collector.
[0047] The alumina / silica-based fiber precursor can be collected and accumulated using an accumulation device that has a structure in which an endless belt made of wire mesh is placed at approximately right angles to the spinning airflow and the spinning airflow containing the alumina / silica-based fiber precursor is collided with the endless belt while the belt is rotating, and the alumina / silica-based fiber precursor can be recovered as a continuous sheet-like accumulation (thin sheet) of the alumina / silica-based fiber precursor.
[0048] The basis weight of this thin sheet is preferably 10 to 200 g / m 2 , particularly preferably 30 to 100 g / m 2 To an extent, but not limited to this.
[0049] The thin sheets collected from the stacking device can be further stacked. Specifically, for example, a stack (thin sheet) of inorganic fiber precursors can be continuously drawn out and fed to a folding device, folded to a predetermined width, stacked, and continuously moved in a direction perpendicular to the folding direction to form a stacked stack (laminated sheet) of inorganic fiber precursors. By stacking the thin sheets in this way, the basis weight (weight per unit area) of the laminated sheet becomes uniform over the entire sheet. As the folding device, one described in JP-A-2000-80547 can be used.
[0050] <Needling aid or antifriction agent application process> A needling aid or antifriction agent is applied to the sheet surface of the thin layer sheet or laminated sheet of the alumina / silica-based inorganic fiber precursor obtained by spinning, if necessary. The needling aid or antifriction agent is preferably applied to both sheet surfaces.
[0051] The needling aid is not particularly limited as long as it has the effect of strengthening the threads near the matte surface of the inorganic fiber precursor aggregate, and various coating agents, for example, acrylic polymer coating agents, can be used.
[0052] The antifriction agent may be a surfactant or emulsion that reduces friction between the needle and the fiber. The needling aid or antifriction agent is applied by applying a solution or dispersion (wet coating).
[0053] <Needling process> A needling aid and / or antifriction agent is added to the laminated sheet of the alumina / silica-based inorganic fiber precursor obtained by spinning, if necessary, and then the laminated sheet is subjected to a needling treatment in which needles having barbs are inserted into and removed from the laminated sheet. The needling treatment may be performed from only one side of the laminated sheet or from both sides. It is preferably performed from both sides.
[0054] The needles are preferably inserted in a direction perpendicular to the surface of the laminate sheet. The needles are inserted deeper than the center of the laminate sheet in the thickness direction. The needles may be inserted so as to penetrate the laminate sheet in the thickness direction.
[0055] In this way, needle marks are formed on the inorganic fiber molded body by the needling process. That is, when the needling process is performed by piercing and removing needles with barbs into and from the laminated sheet, at least some of the fibers are extended in the approximate thickness direction by the needles at the locations where the needles are pierced and removed. This forms needle marks on the surface of the inorganic fiber molded body. The inorganic fiber threads extending in the approximate thickness direction inside the inorganic fiber molded body that has been subjected to the needling process are called warp threads.
[0056] The needling treatment is carried out in order to adjust the bulk density and peel strength of the inorganic fiber molded product by forming warp threads.
[0057] The needle marks may penetrate the inorganic fiber molding, or may penetrate from one matte surface and extend so as not to reach the other matte surface.
[0058] <Firing process> The inorganic fiber molded body is preferably a fired body obtained by firing an inorganic fiber precursor that has been subjected to a needling treatment. The firing is usually performed at a temperature of 900°C or higher, preferably 1000 to 1300°C. A firing temperature of 900°C or higher is preferable because crystallization proceeds sufficiently and alumina / silica-based fibers with excellent strength can be obtained. A firing temperature of 1300°C or lower is also preferable because grain growth of the fiber crystals does not proceed too much and alumina / silica-based fibers with appropriate strength can be obtained. EXAMPLES
[0059] [Example 1] <Production of inorganic fiber molded body> Silica sol was added to an aqueous solution of basic aluminum chloride (aluminum content 165 g / L, Al / Cl = 1.8 (atomic ratio)) so that the final composition of the alumina fiber would be Al2O3:SiO2 = 72:28 (weight ratio). Polyvinyl alcohol was then added and the mixture was concentrated to prepare a spinning solution with a viscosity of 70 poise (25°C) and an alumina / silica content of approximately 35% by weight.
[0060] The spinning solution was spun by the blowing method. The spinning nozzle used was the same structure as that shown in FIG. 6 of Japanese Patent No. 2602460. In addition, when collecting the fibers, an endless belt made of wire mesh was installed at a right angle to the spinning airflow, and the fibers were collected as a continuous sheet (thin sheet) by a collecting device having a structure in which the spinning airflow containing the alumina / silica fiber precursor was collided with the endless belt while rotating.
[0061] The thin sheets collected from the stacking device were sprayed with a lubricant, and then continuously pulled out and fed to a folding device, where they were folded to a specified width and stacked while being continuously moved in a direction perpendicular to the folding direction to form a laminated sheet. The folding device used was a folding device with a structure similar to that described in JP-A-2000-80547. The needling process was performed by punching using a needle punching machine.
[0062] It is then fired at 1200°C and has a basis weight of 900g / m 2 (Thickness 5.6mm, bulk density 0.16g / cm 3 ) to obtain an inorganic fiber molded body 1 made of crystalline alumina / silica fibers. Firing was performed in an electric furnace at a temperature increase rate of 5°C / min up to 1200°C, and after holding at 1200°C for 30 minutes, the material was naturally cooled.
[0063] The composition ratio of this crystalline alumina / silica-based fiber was alumina / silica = 72 / 28 (weight ratio), and the average fiber diameter of the crystalline alumina / silica-based fiber (average value of 100 fibers) measured by observing the inorganic fiber molding under a microscope was 5.5 μm.
[0064] <Manufacture of battery pack covers> The obtained inorganic fiber molded body and an aluminum alloy plate (Al alloy plate A5052, thickness 0.8 mm) serving as a cover substrate were overlapped to form a laminate, thereby producing a battery pack cover 1 of Example 1.
[0065] [Example 2] In Example 1, the inorganic fiber molded body having a reduced fiber amount per unit area was manufactured with a basis weight of 600 g / m 2 (Thickness 4.8mm, bulk density 0.12g / cm 3 ), an inorganic fiber molded body 2 was produced in the same manner as in Example 1, and an aluminum alloy plate (Al alloy plate A5052, thickness 0.8 mm) was overlaid to form a laminate, thereby producing a battery pack cover 2 of Example 2. The composition ratio of this crystalline alumina / silica-based fiber was alumina / silica = 72 / 28 (weight ratio), and the average fiber diameter (average value of 100 fibers) of the crystalline alumina / silica-based fiber measured by observing the inorganic fiber molded body with a microscope was 5.5 μm.
[0066] [Example 3] In Example 1, the needle mark density was reduced to reduce the bulk density, and the basis weight was 900 g / m 2 (Thickness 6.3 mm, bulk density 0.14 g / cm 3), an inorganic fiber molded body 3 was produced in the same manner as in Example 1, and an aluminum alloy plate (Al alloy plate A5052, thickness 0.8 mm) was overlaid to form a laminate, thereby producing a battery pack cover 3 of Example 3. The composition ratio of this crystalline alumina / silica-based fiber was alumina / silica = 72 / 28 (weight ratio), and the average fiber diameter (average value of 100 fibers) of the crystalline alumina / silica-based fiber measured by observing the inorganic fiber molded body with a microscope was 5.5 μm.
[0067] [Example 4] As the inorganic fiber molded body 4, Arsen NBK80-10 manufactured by Denka Co., Ltd. was used. The composition ratio of the crystalline alumina / silica-based fibers was alumina / silica = 80 / 20 (weight ratio), and the average fiber diameter (average value of 100 fibers) of the crystalline alumina / silica-based fibers measured by observing the inorganic fiber molded body with a microscope was 4.4 μm. The inorganic fiber molded body 4 and an aluminum alloy plate (Al alloy plate A5052, thickness 0.8 mm) were overlapped to form a laminate, and the battery pack cover 4 of Example 4 was manufactured.
[0068] [Example 5] As the inorganic fiber molded body 5, FMX16 Blanket LXS150 manufactured by ITM Co., Ltd. (currently Isolite Kogyo Co., Ltd.) was used. The composition ratio of this crystalline alumina / silica-based fiber was alumina / silica = 72 / 28 (weight ratio), and the average fiber diameter (average value of 100 fibers) of the crystalline alumina / silica-based fiber measured by observing the inorganic fiber molded body with a microscope was 4.1 μm. The inorganic fiber molded body 5 and an aluminum alloy plate (Al alloy plate A5052, thickness 0.8 mm) were overlapped to form a laminate, and the battery pack cover 5 of Example 5 was manufactured.
[0069] [Example 6] In Example 1, the inorganic fiber molded body having a reduced fiber amount per unit area has a basis weight of 432 g / m 2 (Thickness 3.5mm, bulk density 0.12g / cm 3), an inorganic fiber molded body 6 was produced in the same manner as in Example 1, and an aluminum alloy plate (Al alloy plate A5052, thickness 0.8 mm) was overlaid to form a laminate, thereby producing a battery pack cover 6 of Example 6. The composition ratio of this crystalline alumina / silica-based fiber was alumina / silica = 72 / 28 (weight ratio), and the average fiber diameter (average value of 100 fibers) of the crystalline alumina / silica-based fiber measured by observing the inorganic fiber molded body with a microscope was 5.6 μm.
[0070] [Comparative Example 1] The inorganic fiber molded body 1 obtained in Example 1 was crushed and broken into short fibers using a dry type fiber defibrator. Water was added to 92.4% by weight of the inorganic fibers to prepare a dispersion. 6.0% by weight of modified acrylic acid ester copolymer (latex), 0.5% by weight of anionic acrylic resin (paper strength agent), 1.0% by weight of aluminum sulfate, and 0.1% by weight of polymer flocculant were added to this dispersion, and the mixture was agglomerated and stirred to prepare a slurry. The slurry was dried using a papermaking machine to obtain a basis weight of 700 g / m2. 2 (Thickness 5.3 mm, bulk density 0.13 g / cm 3 The suction speed and the slurry supply speed were adjusted so that the suction speed was 0.8 mm.) The inorganic fiber molded body was then obtained. The inorganic fiber molded body and an aluminum alloy plate (A5052 Al alloy plate, thickness 0.8 mm) were then stacked to form a laminate, thereby producing the battery pack cover of Comparative Example 1.
[0071] <Measurement of physical properties of inorganic fiber molded body> The inorganic fiber molded products obtained in the above Examples and Comparative Examples were measured for tensile strength, fiber length, thickness, and needle mark density as follows. The results are shown in Table 1.
[0072] Tensile strength measurement test method Measurements were made using a tensile tester. The size of the parallel part (effective part) of the test piece was 25 mm x 100 mm, and the overall size was 25 mm x 160 mm. The inorganic fiber molded product was cut to the above size using a punching die, attached to the tensile tester, and pulled at a speed of 25 mm / min. The maximum load was defined as the tensile strength.
[0073] Average fiber length measurement method Average fiber length measurement method Measured using an optical microscope. Measured using an optical microscope. 2 g of sample was taken from the inorganic fiber molded body with tweezers and put into a 1000 ml beaker with 800 ml of water. Ultrasonic dispersion was performed using a Tokyo Rikakikai device (model: USC-200Z38S-23), and then 20 to 25 ml of the dispersed liquid was taken and put into a 200 ml beaker containing 150 ml of water to prepare a sample liquid. The sample liquid was strongly stirred with a stirrer, 1 to 2 ml was taken and dropped onto a slide glass, a cover glass was placed on it, and the fibers displayed on the microscope monitor were read in 1 mm increments to the length. The number of samples was 300, and the length of each fiber was calculated using the following conversion formula. Conversion formula: fiber length (μm) = measured value (mm) ÷ magnification × 1000
[0074] How to measure thickness The measurement was performed using a digital dial gauge. The measurement load was 4.9 kPa (50 g / cm 2 ) and the minimum measurement scale is 0.01 mm. The thickness of a test piece cut out by the method described in the flame test method described later was measured at five random points using the measuring tool, and the average value of the five points was used as the representative value of the measurement.
[0075] -Method for measuring needle mark density The number of needle marks per unit area was determined as the average of the number of needle marks on one peeled surface of an inorganic fiber molded body cut into a unit area and peeled from the center of the thickness of the inorganic fiber molded body, and the number of needle marks on the other peeled surface. The area where the warp threads existed was counted as the needle marks.
[0076] In practice, when visible light is applied to one side of an inorganic fiber molding, transmitted light is observed on the peeled surface. By counting the number of light spots and warp threads that are transmitted to the peeled surface, the number of all needle marks per unit area can be counted.
[0077] The needle mark density of Example 1 and Example 2 was measured by the above method, and was found to be 27.3 / cm 2 , 19,3 pieces / cm 2 It became.
[0078] <Flame test method> The inorganic fiber molded bodies 1 to 8 of Examples 1 to 7 and Comparative Example 1 were cut into 3600 mm pieces using a punching die. 2 The cut inorganic fiber molded bodies were cut into pieces of each aluminum alloy plate (3600 mm 2 The test pieces were stacked with two sheets of paper (0.8 mm thick) and subjected to the following flame test.
[0079] The test specimen was clamped and fixed in a stainless steel jig and placed 70 mm away from the tip of the torch burner. The test specimen was placed so that the inorganic fiber molded body side faced the burner and the matte surface of the inorganic fiber molded body was approximately perpendicular to the axial direction of the burner.
[0080] This torch burner (Sakaguchi Manufacturing: WT-01, nozzle diameter 1.2 mm) was supplied with O20.5 MPa, C2H20.02 MPa, and air pressure of 0.2 MPa (discharge) from the air nozzle. Flame and air were supplied for 5 minutes using an air nozzle (with a nozzle diameter of 3.0 mm and positioned 100 mm away from the test specimen so that the matte surface of the inorganic fiber molding was approximately perpendicular to the axial direction of the air nozzle), and a flame at a temperature of 1000°C was sprayed toward the test specimen.
[0081] The test piece was removed 5 minutes after the start of irradiation of the inorganic fiber molded body with the flame, and it was visually confirmed whether or not the inorganic fiber molded body had been penetrated by the flame. The results are shown in Table 1.
[0082] [Table 1]
[0083] <Consideration> As shown in Table 1, the battery pack cover of the present invention has excellent flame barrier properties, since flames do not penetrate the inorganic fiber molding.
[0084] Although the present invention has been described in detail with reference to specific embodiments, it will be apparent to those skilled in the art that various modifications can be made without departing from the spirit and scope of the invention. This application is based on Japanese Patent Application No. 2020-206897, filed on December 14, 2020, the entirety of which is incorporated by reference. [Explanation of symbols]
[0085] 1 Battery pack unit 2. Housing 3 Battery pack cover 4. Inorganic fiber molding 5 Cover material 10 Battery Pack 11 Battery Module
Claims
1. A battery pack cover for use in a battery pack, comprising: A cover substrate; and an inorganic fiber molded body having a tensile strength of 20N or more in the following tensile test, The inorganic fiber molded body is a needle blanket, The inorganic fiber molded body is not permeable in a flame test at a flame temperature of 1000° C. for 5 minutes, The inorganic fiber molded body is composed of inorganic fibers having an average fiber length of 3 mm or more, The inorganic fibers are crystalline alumina / silica-based fibers, The crystalline alumina / silica fiber has an alumina / silica composition ratio (weight ratio) of 60 to 95 / 40 to 5; A battery pack cover characterized in that an additional layer is not provided on the surface of an inorganic fiber molded body opposite to the cover substrate (except for those having a passive insulating material containing a plurality of insoluble fibers). <Tensile test> A test piece 25 mm wide x 160 mm long is cut out from the inorganic fiber molded product, and the test piece is pulled in the longitudinal direction at a speed of 25 mm / min using a tensile tester. The maximum load measured is taken as the tensile strength.
2. A battery pack cover for use in a battery pack, comprising: A cover substrate; and an inorganic fiber molded body having a tensile strength of 20N or more in the following tensile test, The inorganic fiber molded body is a needle blanket, The inorganic fiber molded body is not permeable in a flame test at a flame temperature of 1000° C. for 5 minutes, The inorganic fiber molded body is composed of inorganic fibers having an average fiber length of 3 mm or more and 7.9 mm or less, The inorganic fibers are crystalline alumina / silica-based fibers, A battery pack cover (excluding those having a passive insulation material containing a plurality of insoluble fibers) characterized in that the crystalline alumina / silica-based fiber has an alumina / silica composition ratio (weight ratio) of 60 to 95 / 40 to 5. <Tensile test> A test piece 25 mm wide x 160 mm long is cut out from the inorganic fiber molded product, and the test piece is pulled in the longitudinal direction at a speed of 25 mm / min using a tensile tester. The maximum load measured is taken as the tensile strength.
3. 3. The battery pack cover according to claim 1, wherein the cover substrate is a metal substrate or a reinforced resin substrate.
4. The battery pack cover according to claim 1 , wherein the inorganic fiber molded body is disposed on a side closer to the battery pack than the cover base material.
5. 5. The battery pack cover according to claim 1, wherein the inorganic fiber molded body is directly laminated on the cover base material.
6. The battery pack cover according to claim 1 , wherein the needle blanket is a nonwoven fabric of inorganic fibers that has been subjected to a needling process.
7. A battery pack cover described in any one of claims 1 to 6, excluding the embodiment in which the inorganic fiber molding is impregnated with a hydrous adhesive-type heat remover composition and the embodiment in which the hydrous adhesive-type heat remover composition is provided on the surface of the inorganic fiber molding.
8. A battery pack cover described in any of claims 1 to 7, wherein the inorganic fiber molding is an inorganic fiber molding having a tensile strength of 21.5 N or more in a tensile test.
9. A battery pack unit comprising the battery pack cover according to any one of claims 1 to 8 and a battery pack.
10. An electric mobility device comprising the battery pack unit according to claim 9.
Citation Information
Patent Citations
Battery pack gas exhaust system
EP2506336A1
Composite material and manufacture thereof
JP1985239232A
Device for partitioning atmosphere in horizontal type continuous annealing furnace
JP1996291339A
Holding seal material and exhaust gas treating device
JP2007127112A
Composite material having a heat removal property and safeguarding container using the same
JP2019123100A